Exploring Race Differences in Satisfaction With Rehabilitation Following Total Knee Arthroplasty: A Qualitative Study. Issue 2 (11th May 2021) - Bove, Allyn M; Dong, Erin; Hausmann, Leslie R M; Piva, Sara R; Brach, Jennifer S; Lewis, Allen; Fitzgerald, G Kelley
Abstract: Background: The purpose of this qualitative focus group study was to explore race differences in the rehabilitation experience and satisfaction with rehabilitation following total knee arthroplasty (TKA). Method: We conducted a series of qualitative focus group discussions with groups of non-Hispanic White and non-Hispanic Black older adults who recently underwent TKA. We used grounded theory approach, which asks the researcher to develop theory from the data that are collected. Participants discussed barriers and facilitators to accessing rehabilitation after surgery, opinions regarding their physical therapists, the amount of postoperative physical therapy received, and overall satisfaction with the postoperative rehabilitation process. Results: Thirty-six individuals participated in focus groups. Three major themes emerged: (i) Participants reported overall positive views of their post-TKA rehabilitation experience. They particularly enjoyed one-on-one care, the ability to participate in "prehabilitation, " and often mentioned specific interventions they felt were most helpful in their recovery. (ii) Despite this, substantial barriers to accessing physical therapy exist. These include suboptimal pain management, copayments and other out-of-pocket costs, and transportation to visits. (iii) There were minor differences in the rehabilitation experiences between Black and White participants. Black participants reported longer paths toward surgery and occasional difficulty interacting with rehabilitation providers. Conclusions: Individuals undergoing TKA can largely expect positive rehabilitation experiences postoperatively. However, some barriers to postoperative physical therapy exist and may differ between Black and White patients. Physical therapists should increase their awareness of these barriers and work to minimize them whenever possible.